AMAR MA’RUF DAN NAHI MUNKAR (Suatu Pendekatan Hadis Dakwah dalam Perubahan Sosial) - Muhammad Sabir (Potret Pemikiran, 2018)
Prophet of Muhammad saw was commanded to missionize in Mekkah to the Arab community. This mission movement brought social change that happened in the field of religion, moral, and law. Prophet of Muhammad saw was delegated to perform amarma’ruf (goodness command) and Nahi Munkar (forbidden goodlessness), fought to against injustice and arbitrary was done by Arab community of Jahiliyah in Makkah. Prophet of Muhammad saw came free human being of behavior, moral, errant, grind, slavery, social difference, and build society pursuant to belief in Allah swt. Prophet of Muhammad saw performed mission confronted to condition of society which obeyed to tradition. Powers and conglomerate pout, affronting that Muhammad came from impecunious family, illiteracy and orphan. Nevertheless, Prophet of Muhammad saw was always determined, and patient perform mission even though was affronted and reputed crazy.Performed by revolution Prophet of Muhammad saw was revolution totally touching all human life aspect, touching behavior of jahiliyah intent on civilization, virulent intent on good behavior, slavery go to brotherhood, insincerity go to trust, grind of woman clan go to clarification and order free life human being in compliance to Allah. Attendance of Prophet of Muhammad gave bliss and expectation for all human being, even all creatures exists in this earth. Keywords: Mission, goodness command, forbiddengodlessness, the Arab community. Nabi Muhammad saw, diperintahkan berdakwah kepada kaum Arab di Makkah. Gerakan dakwah ini membawa perubahan sosial yang terjadi dalam bidang agama, moral, dan hukum.Nabi Muhammad saw, di utus untuk menjalankan amar ma’ruf dan Nahi Munkar melawan ketidakadilan, dan kesewenang-wenangan yang dilakukan oleh komunitas Arab Jahiliyah di Makkah. Nabi Muhammad saw, datang untuk membebaskan manusia dari akhlak, moral, kesesatan, penindasan, perbudakan, kesenjangan sosial, dan membangun masyarakat berdasarkan keimanan kepada Allah. Nabi Muhammad saw dalam menjalankan dakwah dalam kondisi masyarakat yang taat kepada tradisi jahiliyyah. Penguasa, dan konglomerat mencibirkan, menghina bahwa Muhammad berasal dari keluarga miskin, yatim dan buta huruf. Meskipun demikian, Nabi Muhammad saw selalu tabah, dan sabar menjalankan dakwahnya meski harus dihina dan dianggap gila. Revolusi yang dilakukan Nabi Muhammad saw adalah revolusi menyeluruh yang menyentuh segala aspek kehidupan manusia, menyentuh perilaku jahiliyah menuju peradaban, jahat menuju perilaku baik, perbudakan menuju persaudaraan, kecurangan menuju kepercayaan, penindasan kaum perempuan menuju pencerahan dan menyuruh manusia hidup bebas dalam kepatuhan kepada Allah. Kehadiran Nabi Muhammad memberi harapan dan kebahagiaan bagi seluruh manusia, bahkan seluruh makhluk yang ada di bumi ini. Kata Kunci: Dakwah, Amr Ma`ruf dan Nahi Munkar, Masyarakat Arab